Pengamanan Portable Document Format (PDF) Menggunakan Algoritma Kriptografi Kurva Eliptik - Gever Imanuel Taopan; Meiton Boru; Adriana Fanggidae (J-ICON : Jurnal Komputer dan Informatika, 2022)
The use of digital documents has been widely used in various groups, organizations or agencies. One of the digital documents that often used is the Portable Document Format (PDF). An algorithm needed to implemented in the software, so that it can secure these documents from parties who can harm. One of the algorithms that can be used is Elliptic Curve Cryptography (ECC). ECC has an advantage on the level of data security with a key not too long. Encryption carried out on a 16 Bytes PDF header using 7 ECC parameters, prime number, coefficient A, coefficient B, base point, secret key, public key and K. The prime numbers used are 67, 71, 151, 199, 229, and 239. Other parameters chosen randomly. Each prime number involved for encryption of 4 types of file size, 1KB-2MB, 2MB-4MB, 4MB-6MB, and more than 5MB, where each type of file size has 5 different files. There were 3 trials for each file, so there were 360 trials. The 360 trials, there were ±55.33% in the very low correlation class, ±34.72% in the low class, ±10% in the medium class and ±1.94% in the strong class. Overall the average correlation generated is 0.212282779. Therefore, the use of the ECC algorithm for encryption the header of PDF is quite good. In the encryption process there is also an increase in file size by 64 Bytes, but when decrypting the file size returns to its original size.